A Review of Elderly Care in India: Challenges, Solutions, and a Comparative Analysis with Japan - Kumar Singh, Abhishek; Singh, Ashish Kumar; R S, Varun; Singh, Monica; M Singari, anganath (Journal of Neonatal Surgery, 2025)
This research paper delves into the intricate domain of elderly care in India, responding to the imperative posed by the nation's swiftly aging population. The study unfolds through a three-fold exploration, commencing with a thorough analysis of the challenges faced by the elderly in India. It progresses to offer a strategic roadmap for establishing and managing elderly care homes, addressing the evolving needs of this demographic. The comparative analysis with Japan provides a global perspective, highlighting diverse approaches in cultural, demographic, and policy contexts. The challenges in elderly care are rooted in the shifting dynamics of family structures and the increasing life expectancy of the aging population. Social isolation, healthcare access disparities, and safety concerns emerge as focal points, necessitating holistic solutions. The rise of professional elderly care homes becomes pivotal, catering to the unique healthcare needs of the elderly and ensuring a secure and supportive environment. The strategic roadmap outlined in this research paper provides a comprehensive guide for establishing successful elderly care homes in India. Market research, feasibility studies, and a well-defined business plan serve as foundational elements. Legal compliance, optimal location selection, and meticulous staffing considerations are emphasized. Financial planning, safety and security measures, and a commitment to quality of life services contribute to the viability and sustainability of elderly care homes. The comparative analysis with Japan enriches the discussion, unraveling unique demographic challenges, family structure transformations, and cultural nuances in both countries. Healthcare infrastructure, government programs, and policy differences further underscore the distinctive approaches to elderly care. The conclusion resonates with a call for continuous adaptation, recognizing that the journey towards effective elderly care is dynamic and demands a commitment to evolving strategies alongside the changing needs of seniors. This research paper serves as a valuable resource for individuals and organizations seeking to address the growing need for elderly care in India. By unraveling challenges, proposing strategic solutions, and providing a comparative lens with Japan, the study contributes to a nuanced understanding of elderly care in different societal contexts. The evolving landscape of elderly care requires a commitment to adaptability and improvement, ensuring the well-being and dignity of the aging population